Validitas Media Pembelajaran Berbasis Android Menggunakan APPYPIE Untuk Kemandirian Belajar Siswa Kelas X SMA/MA - Helpian, Helpian; Hurriyah, Hurriyah; Sasminelwati, Sasminelwati (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Android-based learning media is a way to deliver material in the teaching and learning process using Android as a tool, almost all students now have a smartphone, but only used for social media, playing games and sending instant messages such as WhatsApp, very rarely used in the learning process, so it will it is better if the smartphone is used as a learning medium, one of which is by making learning media in the form of applications using appypie. The application in this study contains competencies, teaching materials, sample questions, learning videos, quizzes and verses of the Qurâ€™an related to the subject. The research method used is Research and Development (RnD) with the development process using the 4D model (Define, Design, Develop and Desseminate). This study is to look at the validation of the media application for the independence of student learning.the results of this study indicate that Appypie-based media are valid in language, material and appearance, and can be recommended to support student learning independenceÂ